Optimalisasi Silika Gel Dari Sekam dan Jerami Padi Ditinjau Dari Rasio Bahan Baku dan Konsentrasi H2SO4 dengan Metode Ekstraksi - Permata Sari, Shefia Dian; Meidinariasty, Anerasari; Apri Mujiyanti (Jurnal Serambi Engineering, 2026)
This research aims to optimize silica gel synthesis from rice husk and rice straw through variations in raw material ratio and sulfuric acid concentration. Silica gel was produced through alkaline extraction using NaOH followed by precipitation with H₂SO₄. Variations in husk–straw composition (100:0, 75:25, 50:50, 25:75) and H₂SO₄ concentrations (1 M, 2 M, 3 M) were tested to evaluate their effects on moisture content, water vapor adsorption capacity, pH, and functional groups by FTIR. Results show that the 75% husk–25% straw ratio with 3 M H₂SO₄ yields the optimal silica gel characteristics, including the lowest moisture content, highest adsorption capacity, and stable pH. FTIR analysis confirms the formation of silanol and siloxane functional groups, indicating successful synthesis. This study demonstrates that agricultural waste can be converted into high-quality silica gel through optimized extraction parameters.